PENGEMBANGAN MEDIA VIDEO TUTORIAL BERBASIS ANIMASI DALAM PEMBELAJARAN GARDU INDUK TENAGA LISTRIK KELAS XI DI SMK NEGERI 1 LUBUK PAKAM - Fauzi H Sitorus Pane; Muhammad Amin (JEVTE: Journal of Electrical Vocational Teacher Education, 2021)
Abstract This study aims to: (1) Know how to develop Electric Power Substation Learning Media class XI majoring in Electrical Power Grid Engineering at SMK Negeri 1 Lubuk Pakam, (2) Knowing the feasibility level of Electric Power Substation Learning Media class XI majoring in Electrical Power Network Engineering at SMK Negeri 1 Lubuk Pakam.Abstract must reflect the overall substance of the article content and be able to help readers determine its relevance to their interests and decide whether to read the document in its entirety. This research is included in Research and Development (R&D). This media manufacturing procedure includes (1) Analysis of the product to be developed, (2) Developing the initial product, (3) Expert validation and revision, (4) Small-scale field test and product revision, (5) Large-scale field test and final produc. The development of this product uses Video Scribe software. Product data in the form of qualitative data obtained from the advice and input of media experts, material experts, teachers and students, as well as quantitative data derived from the assessment of media experts, material experts, teachers and students. The results of this study are: (1) making video media tutorial electric power substation steps include, making product design developed, collecting supporting materials for electric power substation materials, finishing, media assessment by media and material experts, revisions, small-scale trials and large-scale trials. (2) The feasibility result of video tutorial media based on animation using Video Scribe software as follows: media expert assessment obtained a score of 4.86 with a very decent category, material expert assessment gets a score of 4.46 with a very decent category, small-scale test assessment gets a score of 4.34  Key Words: Development of learning media, electric power substation. AbstrakPenelitian ini bertujuan untuk : (1)  Mengetahui cara pengembangan Media Pembelajaran Gardu Induk Tenaga Listrik kelas XI jurusan Teknik Jaringan Tenaga Listrik di SMK Negeri 1 Lubuk Pakam, (2) Mengetahui tingkat kelayakan Media Pembelajaran Gardu Induk Tenaga Listrik kelas XI jurusan Teknik Jaringan Tenaga Listrik di SMK Negeri 1 Lubuk Pakam. Penelitian ini termasuk dalam Penelitian dan Pengembangan (Research and Development (R&D)). Prosedur pembuatan media ini meliputi (1) Analisis produk yang akan dikembangkan, (2) Mengembangkan produk awal, (3) Validasi ahli dan revisi, (4) Uji lapangan skala kecil dan revisi produk, (5) Uji lapangan skala besar dan produk akhir. Pengembangan produk ini menggunakan software Video Scribe. Data produk berupa data kualitatif yang didapat dari saran dan masukan ahli media, ahli materi, guru dan siswa,serta berupa data kuantitatif yang berasal dari penilaian ahli media, ahli materi,guru dan siswa. Hasil penelitian ini adalah : (1) pembuatan media video tutorial gardu induk tenaga listrik  langkah-langkahnya meliputi, membuat desain produk yang dikembangkan, mengumpulkan bahan-bahan pendukung untuk materi gardu induk tenaga listrik, finishing, penilaian media oleh ahli media dan materi, revisi, uji coba skala kecil dan uji coba skala besar. (2) Hasil kelayakan media video tutorial berbasis animasi dengan menggunakan software Video Scribe sebagai berikut : penilaian ahli media diperoleh nilai 4,86 dengan kategori sangat layak, penilaian ahli materi mendapatkan nilai sebesar 4,46 dengan kategori sangat layak, penilaian uji skala kecil mendapatkan nilai sebesar 4,34 dengan kategori sangat layak, penilaian uji skala besar mendapatkan nilai sebesar 4,17 dengan kategori sangat layak. Kata Kunci: Pengembangan media pembelajaran, gardu induk tenaga listrik.